COMPARISON OF DRUG-ELUTING STENTS VERSUS BARE METAL STENTS FOR THE TREATMENT OF CORONARY ARTERY DISEASE - KHAN , B; KHAN, AT; MUHAMMAD, A; SAWAR , S; RAHMAN , F; HASSAN , M (Biological and Clinical Sciences Research Journal, 2023)
Coronary artery disease is a condition that affects millions of people worldwide and can lead to serious complications such as heart attack or stroke. The study’s main objective is to compare drug-eluting stents versus bare-metal stents for treating coronary artery disease. The present study aimed to compare the efficacy and safety of drug-eluting stents (DES) versus bare metal stents (BMS) for the treatment of coronary artery disease (CAD). The study was conducted at two tertiary care hospitals, Hayatabad Medical Complex and Lady Reading Hospital in Peshawar, Pakistan, from July 2019 to July 2020. The study included a total of 384 patients with CAD who underwent percutaneous coronary intervention (PCI) with either DES or BMS. The study included a total of 384 patients with CAD who underwent PCI with either DES or BMS. The mean age of the study participants was 58.2 ± 9.4 years, and 75.8% were male. The baseline characteristics, including demographic data, clinical presentation, cardiovascular risk factors, and angiographic findings, were comparable between the two groups. In conclusion, our study contrasting medication-eluting stents versus exposed metal stents for treating coronary supply route sickness found that drug-eluting stents were related to a lower chance of unfriendly heart occasions, including objective vessel revascularization, dead myocardial tissue, and cardiovascular demise, contrasted with uncovered metal stents.